1994
DOI: 10.1037/0012-1649.30.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual correlates of marital change across the transition to parenthood.

Abstract: To explore multiple prenatal antecedents and postnatal correlates of change in marital adjustment and satisfaction in men and women across the transition to parenthood, 102 couples from diverse sociocultural backgrounds were studied longitudinally from pregnancy to the 9th postpartum month. Guided by an ecological model, the pre-and postnatal assessments included questionnaires of marital adjustment, personality traits, attitudes toward parenthood, work role centrality, social support, as well as observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
104
1
16

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 71 publications
13
104
1
16
Order By: Relevance
“…Cowan and Cowan (2000) reported similar results, but here the negative effect of parenthood on the partners' relationship was mainly mitigated by the degree of discrepancy between prenatal expectations and actual father involvement, that is, the violated expectations described by Belsky (1985). It seems that violated expectations of father involvement in childrearing are especially critical for the development of marital quality, so caring for the baby produces most of the new and pressing demands that partners face when becoming parents (Feldman, 2000;goldberg & PerryJenkins, 2004;Levy-Shiff, 1994).…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Cowan and Cowan (2000) reported similar results, but here the negative effect of parenthood on the partners' relationship was mainly mitigated by the degree of discrepancy between prenatal expectations and actual father involvement, that is, the violated expectations described by Belsky (1985). It seems that violated expectations of father involvement in childrearing are especially critical for the development of marital quality, so caring for the baby produces most of the new and pressing demands that partners face when becoming parents (Feldman, 2000;goldberg & PerryJenkins, 2004;Levy-Shiff, 1994).…”
supporting
confidence: 58%
“…However, this argument does not explain the decrease in marital satisfaction experienced by father 1 . As Levy-Shiff (1994) remarks, a decrease in the father's satisfaction may have two complementary explanations. On the one hand, a greater amount of time spent caring for her baby may be linked to a reduction in a mother's involvement in her marital relationship, and these changes may affect the father negatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of parenthood transition, research has found that how couples deal with the allocation of childcare and other household chores was a strong predictor of adaptation. Issues such as paternal involvement (Levy-Shiff, 1994), violated expectations for the sharing of responsibilities (Hackel & Ruble, 1992), and the process of decision making (Osofsky & Culp, 1989) are all predictive of marital satisfaction for both sexes.…”
Section: Resources For Coping With Parenthood Stressmentioning
confidence: 99%
“…De facto, embora nem todas as mulheres reportem um decrés-cimo da satisfação conjugal depois do nascimento e algumas reportem mesmo um aumento (Delmore-Ko et al, 2000), tem sido consistentemente demonstrado que a satisfação conjugal materna declina quando as expectativas pré-natais não são confirmadas (Levitt et al, 1994). Há também evidência de que, em termos médios, os homens reportam menor decréscimo da satisfação conjugal do que as mulheres (Levy-Shiff, 1994;Dulude et al, 2002) Para além da vida doméstica, o nascimento de um filho implica frequentemente mudanças importantes noutras áreas, tais como finanças, actividades de lazer, relação com os familiares e amigos, e vida profissional, que afectam também os novos pais. No estudo de Ausloos (1996), todos os casais relataram ter passado por um período de crise pessoal durante os primeiros seis meses pós-parto.…”
Section: Introductionunclassified